(untitled) (Baghdad Science Journal, 2005)
Despite the multiple sources of polycyclic compounds in the agricultural environment, this study suggests that it is possible to adopt the events of plants and their associated microorganisms in the soil, such as mushrooms and bacteria in the decomposition of these compounds can also use harvested plants such as barley and alfalfa grown for animal feed